Unresolved Psychological Problem in Dennis Lehane’s Shutter Island - Ahmad Luthfi; Rika Handayani (Andalas International Journal of Socio-Humanities, 2022)
This article explains hallucination as a psychological problem undergone by Andrew Laeddis, the main character of Dennis Lehane’s Shutter Island. Viewed from Sigmund Freud’s psychoanalytical theory (id, ego, and superego), self-defense mechanism theory by Anna Freud, and hallucination theory, this article shows how the main character faces the hallucination and how his efforts fail. The results of the study reveal that Andrew Laeddis faces three types of hallucination: visual hallucination, auditory hallucination, and temporal illusion. Andrew Laeddis also applies two self-defense mechanisms: denial of reality and regression. Since the id is more dominant than the ego, the doctors do not succeed in curing him of the hallucination. In other words, Andrew Laeddis experiences an unresolved psychological problem; which is hallucination.